Enhancing interfacial bonding in friction stir lap welding of light metal and carbon fiber reinforced polymer composite. (November 2022) - Wang, Suyu; Xu, Yuxin; Wang, Wenquan; Tian, Yingtao; Zhang, Xinge; Huang, Hu; Zheng, Daoyou
Abstract: The key strategic technology of automotive lightweight design advances the development of light metal/carbon fiber reinforced polymer composite hybrid joining. In this work, Al alloy (AA6061) and carbon fiber reinforced polyamide 66 (CF-PA66) were joined using friction stir lap welding (FSLW) technique with laser ablation pretreatment. The enhancing interfacial bonding mechanism and failure analysis of hybrid joints were investigated in detail. The maximum tensile-shear strength reached 24.48 MPa based on the bonding mechanism including macro/micro/nano-mechanical interlocking and chemical bonding, increasing by approximately 600 % compared with FSLW joints without surface pretreatment. Fracture located at weak interfaces between metal and composite without laser-textures and mixing region of resin and carbon fibers. This study provides novel insights into material-process-structure integrated lightweight design and benefits future research in the processes to enhance metal/composite hybrid structures. Graphical abstract: Unlabelled Image Highlights: Based on the concept of introducing geometric configuration, regular micro-textures were generated on Al alloy surface; The maximum tensile-shear strength of joints reached 24.48 MPa based on the bonding mechanism including macro/micro/nano-mechanical interlocking and chemical bonding; The friction stir lap welding assisted by pretreatment showed high-level joint efficiency, which was competitive to the other welding methods in joining light metal and composite.